Annihilation or decline: The fall of Anyang as an urban center. (June 2018) - Li, Yung-ti; Yue, Zhanwei; He, Yuling
Abstract: As many scholars have already pointed out, the practice of using historiography to interpret archeological data in Chinese archaeology has limited our approach to understand ancient China. While accounts in historiography provide rich and invaluable textual information, they should be seen as clues for further investigation or hypotheses that need to be tested in the field. Archaeologists have become more self-conscious in their use of historiography, but there are still many hidden assumptions that are not contested in the field of Anyang archaeology. For the current authors, the fall of Anyang as the last capital of the Shang dynasty is one such assumption that needs to be further examined. The historical account of how the Western Zhou conquerors sacked the Shang capital has long been the only scenario used to understand the termination of Anyang. However, mold fragments for casting bronzes seen only in the Western Zhou territory have now been unearthed in Anyang. These finds introduce the possibility that while Anyang was sacked politically as the seat of the Shang ruling elite, the urban center itself may have continued. For instance, the bronze foundry may have been in operation after the fall of the Shang dynasty and manufactured bronze vessels for the newly risen Zhou elite. We therefore propose that it is time to reorient our research approach to study not just the time when the capital fell, but also the process of how Anyang as a Bronze Age mega center disappeared.